Computational studies on nonenzymatic pyroglutamylation mechanism of N-terminal glutamic acid residues in aqueous conditions*. (17th July 2020) - Nakayoshi, Tomoki; Kato, Koichi; Kurimoto, Eiji; Oda, Akifumi
Abstract : Spontaneous cyclisation of glutamic acid (Glu) residues located at N-termini in peptides and proteins is called 'pyroglutamylation' and is assumed to be involved in several neurodegenerative diseases. Although it has long been believed that N-terminal Glu residues undergo pyroglutamylation enzymatically, it has recently been experimentally confirmed that nonenzymatic pyroglutamylation can proceed in some types of aqueous buffer. However, the detailed mechanism has not been proposed or investigated, and even whether some small-molecule catalysts are required for pyroglutamylation has not been clarified. Therefore, we investigated three types of pyroglutamylation mechanism of N-terminal Glu residues using quantum chemical calculations: in the absence of any catalysts, catalysed by one water molecule, and catalysed by two water molecules. All calculations were performed using N-terminal Glu residues capped with a methylamino group on the C-terminal as a model compound. Optimised energy minima and transition state geometries were obtained using the B3LYP density functional method. The pyroglutamylation mechanism is roughly divided into two steps: cyclisation and dehydration, and the calculated activation barrier was 108 and 107 kJ mol −1 in the two- and three-water-assisted pathways, respectively. The results of computational analysis suggest that water molecules can act as catalysts for pyroglutamylation. The calculated activation barrier of two-water-assisted pyroglutamylation was 108 kJ mol −1, and the results of computational analysis indicate that water molecules can act as catalysts for pyroglutamylation. GRAPHICAL ABSTRACT: